Synthesis of dietary lipids from pumpkin (Cucurbita pepo. L) oil obtained by enzymatic extraction: a sustainable approach - Atsakou, Abra Eli [UNESP]; Remonatto, Daniela [UNESP]; Júnior, Rodney Helder Miotti [UNESP]; Paz-Cedeno, Fernando Roberto [UNESP]; Masarin, Fernando [UNESP]; Andrade, Grazielle Santos Silva; de Lucca Gattas, Edwil Aparecida [UNESP]; de Paula, Ariela Veloso [UNESP] (Springer Nature, 2023)
This study aimed to assess the nutritional properties of dietary lipids obtained through the modification of aqueous enzymatically extracted pumpkin seed (Cucurbita pepo. L) oil. The optimal growth conditions for producing pectinase using strain Aspergillus sp. 391 were determined, and partial characterization of pectinase and commercial cellulase was conducted. The enzymatic extraction was performed at pH 4.0, 50 °C, for 24 h, using a combination of pectinase and cellulase for optimum effectiveness. The crude oil obtained was analyzed for acid, peroxide, and fatty acid composition. The study found a high amount of unsaturated fatty acids, mainly linoleic acid (C18:2), and a 59% oil recovery rate. Subsequently, this oil was subjected to enzymatic acidolysis with capric acid in solvent-free media, catalyzed by lipase Lipozyme RM IM®, resulting in a product with a higher incorporation degree (48.39 ± 0.5 mol%), observed after 24 h at 60 °C using molar ratio oil:acid capric of 1:9 (run 4). The nutritional properties of this oil were improved.
Keywords: Acidolysis; Aqueous enzymatic extraction; Aspergillus sp; Dietary lipids; Pumpkin seeds (Cucurbita pepo L) oil; Structured lipids